AG36 Inhibits Human Breast Cancer Cells Proliferation by Promotion of Apoptosis In vitro and In vivo - Mu, Li-Hua; Wang, Yu-Ning; Wang, Dong-Xiao; Zhang, Jing; Liu, Li; Dong, Xian-Zhe; Hu, Yuan; Liu, Ping (Frontiers in Pharmacology, 2017)
AG36 is the biotransformation product of triterpenoid saponin from Ardisia gigantifolia stapf. In this study, the antitumor activity and underlying molecular mechanisms of AG36 against human breast MCF-7, MDA-MB-231, and SK-BR-3 cancer cells were investigated. AG36 inhibited the viability of MCF-7, MDA-MB-231, and SK-BR-3 cells in a dose and time-dependent manner, with an IC50 of approximately 0.73, 18.1, and 23.4 μM at 48 h, respectively. AG36 obviously induced apoptosis and G2/M arrest of all the three breast cancer cells. Moreover, AG36 decreased the protein expression of cycle regulatory proteins cyclin B1 or cyclin D1. In MCF-7 and MDA-MB-231 cells, AG36 strongly increased the cleaved caspase-3 and -8 protein expressions, while in SK-BR-3 cells, AG36 only increased the protein expression of cleaved caspase-3. In all the three breast cancer cells, the ratio of Bax/Bcl-2 and cytosolic cytochrome c content increased significantly compared with control group. The death receptor-related proteins Fas/FasL, TNFR1, and DR5 were detected by Western blot, it showed that different breast cancer cells activated the death receptor-mediated extrinsic caspase-8 pathway through different receptors. In addition, the caspase-8 inhibitor z-IETD-fmk could significantly block AG36-triggered MCF-7 cells apoptosis. The in vivo studies showed that AG36 significantly inhibited the growth of MCF-7 xenograft tumors in BALB/c nude mice comparing with control. In conclusion, AG36 inhibited MCF-7, MDA-MB-231, and SK-BR-3 cells proliferation by the intrinsic mitochondrial and the extrinsic death receptor pathways and AG36 might be a potential breast cancer therapeutic agent.